The global hunger crisis : tackling food insecurity in developing countries - Bne Saad, Majda (Pluto Press, 2013)
"Millions across the world face the daily challenge to find enough food to survive. Hunger is on the rise globally, with more than 1.2 billion people suffering from food insecurity. Rising prices are further restricting food access. In this deeply informative study, Majda Bne Saad identifies the causes for global hunger embedded in the current global political and economic system and highlights the key challenges facing food deficit countries. She shows how Western countries share the blame for global hunger through their support for subsidies to agricultural production and biofuels, which have created new challenges to food security worldwide. Bne Saad argues that, as world population rises from 7 billion to 9.2 billion by 2050, there needs to be a 'second green revolution' to grow more food. She looks at the factors constraining low-income nations from achieving food security and considers policies which could generate income and enhance individuals' entitlement to food."--Publisher's description